Current trends and future directions in probiotics research for HIV/AIDS - Cui, Xinxin; Xie, Zhanpeng; Wu, Zhen; Xu, Li-qin (Frontiers in Microbiology, 2024)
AimThis study aims to comprehensively and systematically review the current status of research on probiotics and HIV/AIDS, while also exploring future research hotspots and trends in this domain.MethodsThe Web of Science (WoS) Core Collection database was queried up until May 13, 2024, to retrieve relevant literature on probiotics and HIV/AIDS. Utilizing CiteSpace, VOSviewers, and Bibliometrix software, scientific achievements and research frontiers in this field were analyzed.ResultsAs of May 14, 2024, a total of 90 articles was included in. The publication output in this area peaked in 2017, with a subsequent decline in the number of articles post-2019. The United States emerged as the leading country in terms of article count (32 articles), with The University of Western Ontario being the institution with the highest publication output. Dr. Reid G contributed the most articles (12 articles). In addition to key terms, high-frequency keywords included immune activation, inflammation, and microbial translocation. The burst analysis of keywords suggests that vaccines may become a focal point of future research.ConclusionFuture research hotspots and trends should focus on elucidating the types of probiotics, intervention timing, and optimal strains (in terms of mixing ratios) in the context of HIV/AIDS. Furthermore, exploration into the role of probiotic metabolites, such as short-chain fatty acids, in vaccine development is warranted.